EFEKTIVITAS MENYIKAT GIGI DENGAN METODE BASS DAN HORIZONTAL TERHADAP PERUBAHAN INDEKS PLAK PADA ANAK TUNAGRAHITA - Nabila Rizkika; Moh. Baehaqi; R. Rama Putranto (Faculty of Dentistry, Universitas Islam Sultan Agung, 2014)
Background: The important aspect for child especially children with mental retardation is oral health. Children with mental retardation have limitations in motoric activities that relate to the actions of dental hygiene in normally, that activities is toothbrushing and it can do by bass and horizontal method. The aim of this study is to know the difference effectiveness toothbrushing with bass and horizontal method on the changed of plaque index in children with mental retardation. Method: The quasi experimental methods with non-equivalent group design with post test design was used in this research and have done on 24 children with mild mental retardation at SDLB Purwosari Kudus which divided two groups, 12 students brushing with bass method and 12 students brushing with horizontal method. Result: The data were tested with paired t-test to compare plaque index before and after toothbrushing with bass and horizontal method, showed that there were meaningful differences (p<0,05). Independent t-test to compare the changed of plaque index between both methods, showed that there were no meaningful differences (p>0,05). Conclusion: It concluded that both bass and horizontal method effectively on the changed of plaque index in children with mental retardation. There was no difference effectiveness between both methods.